ALOX5AP rs10507391 polymorphism and the risk of ischemic stroke in Caucasians: an update meta-analysis - Li, K-L.; Chen, C-Y.; Xu, M.; Zhu, X-Q.; Yang, X-J. (Cellular and Molecular Biology, 2017)
Some reports evaluated the association between ALOX5AP rs10507391 polymorphism and the risk of ischemic stroke in Caucasians. The results remained unknown. Thus, we did a meta-analysis to evaluate this association. Nine case-control studies with 4198 patients and 3699 controls were included in this meta-analysis. A significant association was found between ALOX5AP rs10507391 polymorphism and ischemic stroke risk in Caucasians (OR=1.18; 95%CI, 1.08–1.28; P=0.0002). ALOX5AP rs10507391 polymorphism was associated with ischemic stroke risk in Caucasians from Europe (OR=1.20; 95%CI, 1.09–1.32; P=0.0002) but not from other countries (OR=1.13; 95%CI, 0.95–1.36; P=0.17). No significant association was found between ALOX5AP rs10507391 polymorphism and ischemic stroke risk in males (OR=1.12; 95%CI, 0.91–1.39; P=0.28). Moreover, ALOX5AP rs10507391 polymorphism was not associated with cardioembolic ischemic stroke risk (OR=1.04; 95%CI, 0.73–1.48; P=0.84). In conclusion, this study found that ALOX5AP rs10507391 polymorphism was associated with ischemic stroke risk in Caucasians.